ETHICO-MEDIKOLEGAL EMERGENCY SERVICE - Inge Hartini (UNTAG Law Review, 2019)
Emergency Room (ER) is specific department in the hospital with specific problem too. A true emergency is any condition clinically determined to require immediate medical care. Government has regulation if every health facility must give health care without money deposit and every invasive medical treatment need informed consent.Together, this condition sometimes made unsatisfaction for patient and his family. How applied informed consent, if unconscious patient came without his/her family ? Who must make decision for treatment ?